THE EFFECT OF SOWING DATES AND SEEDLING DENSITY ON THE NUMBER AND MASS OF SUGAR BEET LEAVES - Choriyev Erali Olimovich; Xalikov Baxodir Meylikovich (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
In this article, data and analysis results are presented regarding the effects of sowing dates and plant densities on the number and mass of sugar-beet leaves. It was observed that among the sugar-beet varieties, “Eldona” showed superiority in terms of leaf number and leaf mass, having 2.3–3.1 more leaves and 12.8–14.5 g greater leaf mass compared to the “Sado” variety. Regardless of the variety, when sugar beet was sown during the period of March 20–30, it produced 2.0–2.5 more leaves and 11.0–12.5 g greater leaf mass compared to sowing during April 5–15. Increasing plant density from 83,000 to 166,000 plants per hectare, however, caused the number of leaves to decrease from 6.5 to 12.5 leaves and the leaf mass to decrease from 23.0 g to 36.0 g.